Factors Associated with Service Excellence for Officers in the Batunadua Health Center Service Room - Harahap, Alprida; Wisudawan B, Owildan; Hasibuan, Ahmad Safii (Sean Institute, 2022)
Excellent service can be carried out using various strategies, namely increasing human resources, analyzing people's ability to pay, availability of health facilities/means and analyzing the level of community demand for health services. The purpose of this study was to determine the relationship between education of health workers, service tenure, incentives for health workers and excellent service. This research was conducted inBatunadua Health Center. The type of research used is an analytic survey with a cross sectional study approach. The sample of this study were health workers in inpatients with exhaustive sampling with a total of 67 samples. The results showed that the education of health workers was related to excellent service with a p value (0.031) < 0.05, service tenure of officers was related to excellent service with a p value (0.000) < 0.05, health worker incentives were related to excellent service with a p value (0.001) < 0.05. The conclusion was obtained that the education of health workers, the length of service of the officers, the incentives of health workers were related to excellent service. It is recommended that in providing excellent service to patients, there needs to be fast, precise and pleasant actions without letting the patient wait long.